A new perspective on pore growth in anodic alumina films - Sachiko Ono; Hidetaka Asoh (Electrochemistry Communications, 2021)
In this study, we use advanced analysis techniques to examine the nanostructures of anodic films formed on aluminum in various electrolytes, including oxalic acid and sulfuric acid, in the original state (without being chemically dissolved) and reveal that pores grow with radially branched nanopores. Nanopores are generated in the main pores for the same reason that initial small pores are generated on the film surface: nanopores are created when the electric field is reduced due to the presence of a thick barrier layer. These radially branched nanopores appear in a form characteristic of a film formed in chromic acid, producing a feather-like pore wall. As a representative model, the atypical porous structures created in the film formed in chromic acid were classified into five categories: initial small pores, branched pores, side holes, spherical voids, and radially branched nanopores. We demonstrate that these structures are not unique to chromic acid films but are a universal phenomenon, particularly radial nanobranching, which occurs naturally during the anodizing of most electrolytes.